STATE BUILDING OF THE WUPR IN THE COVERAGE OF THE NEWSPAPER “DROHOBYTSKY LYSTOK” (1918–1919) (Південний архів (історичні науки), 2024)
The purpose of the research is to characterize the coverage of the processes of state building in the Western Ukrainian People’s Republic (Western Region of the Ukrainian People’s Republic) in the newspaper “Drohobytsky Lystok” (“Drohobych Leaf”, 1918–1919). The study did not take into account the foreign policy of the newly created state, the Ukrainian-Polish war, relations with the Ukrainian People’s Republic, the development of local administrative structures in the districts, since these aspects require separate scientific consideration. The research methodology is based on the principles of historicism, systematicity, authorial objectivity, as well as methods of external and internal criticism of historical sources. Research results. It was found that the newspaper characterized the processes of the formation of Ukrainian statehood, primarily the formation of authorities at the national and local levels of the WUPR, the involvement of the public in the resolution of national issues. Information was regularly submitted about the main regulatory and legal acts of the Western Ukrainian parliament and government. Daily meetings of the highest legislative body of WUPR/WR UPR – Ukrainian National Council in Stanislaviv were described. It was established that the newspaper repeatedly criticized the Western Ukrainian government headed by I. Holubovych, reproaching it for the slowness of decisions and failure to resolve urgent social and economic issues. The editors of the magazine advocated the formation of a coalition government (composed of social democrats), and later – for the liquidation of a separate government for the WR UPR and the transfer of powers to manage the western Ukrainian lands to the government of the UPR. In addition, the newspaper “Drohobytsky Lystok” published materials on important areas of the internal policy of the government authorities in WUPR/WR UPR: land reform, ensuring food stability, reconstruction of destroyed housing, etc. Conclusions. The newspaper “Drohobytsky Lystok”, published in Drohobych from November 12, 1918 to May 15, 1919, quite informatively described the processes of state formation on the territory of the WUPR/WR UPR, drawing the attention of readers to the law-making activities of the parliament, decisions and directions of the government's internal policy. Since the editorial staff of the newspaper was headed by a member of the Ukrainian Social Democratic Party, Ivan Kalynovych, the analysis and criticism of events was often carried out from ideological and political positions.
Keywords: newspaper, “Drohobytsky Lystok”, Western Ukrainian People's Republic, state-building processes, Ivan Kalynovych.